Comunicación y discurso cotidiano: Discriminación y violencia en torno al ser mujer indígena en México - Salvador, Cynthia Pech; García, Marta Rizo (Comparative Cultural Studies: European and Latin American Perspectives, 2019)
The aim of this essay is to analyze how racism is present in everyday media messages and in which way it reflects discrimination and violence. Undoubtedly, racism towards indigenous people is an evil entrenched in Mexican society that is objectified in daily interactions, in media representations and in a culture where the indigenous is usually associated to alien and uneducated concepts as well as to a past that is not worth going back. In Mexico, being an indigenous woman leads to a double discrimination: due to gender and ethnic origin. Therefore we strongly believe that it is necessary to reflect on racism and discrimination against this sector of the population in some media discourses.